Implementasi Akuntansi Perpajakan Pada Tenaga Medis - -, Syahruldin; Faidul Adzim; Aldy Arisandi; Muhammad Makbul Gufran; Atika Sapna; Tia Aprilianti (Indonesian Journal of Research in Economy, 2022)
This research aims to explore and evaluate the implementation of tax accounting for medical personnel. This research methodology uses a qualitative approach with descriptive methods. The data obtained comes from observation and documentation. The results of this research analysis highlight the calculation of PPh article 2, article 22, article 23, and VAT carried out by the Bulukumba District Health Service. The findings show that the income tax and VAT calculations carried out by the Bulukumba District Health Service are in accordance with the provisions of Taxation Law No. 26 of 2018. This indicates that the implementation of tax accounting at the Bulukumba District Health Service has been carried out effectively.